Reflexões sobre o brutalismo cearense - Jucá Neto, Clovis Ramiro (2013)
JUCÁ NETO, Clovis Ramiro; ANDRADE, Margarida Julia de Salles; DUARTE JUNIOR, Romeu. Reflexões sobre o brutalismo cearense. In: Seminário DOCOMOMO Brasil, 10., Curitiba, 2013. Anais... Curitiba: PROPAR/UFRGS, 2013.